1969
DOI: 10.1002/1097-0142(196912)24:6<1109::aid-cncr2820240605>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the vital statistics of breast cancer

Abstract: Examination of cross‐sectional and longitudinal age‐specific incidence and mortality rates for breast cancer in the United States and selected areas leads to 3 main findings: 1. Breast cancer incidence and mortality rise sharply during the reproductive years, then continue to rise postmenopausally but at a slower rate; 2. Breast cancer incidence prior to age 55 has increased about 45% since 1935, while above age 55 incidence has remained constant; and 3. There are marked racial and regional differences in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…2, Group II), and confirms similar findings by Shay, Harris and Gruenstein (1960). This characteristic is also shared by human breast cancer, the incidence of which is significantly reduced by oophorectomy before the age of 40 (Feinlieb and Garrison, 1969). This study also suggests that the protective effect of oophorectomy is due to reduction of circulating oestrogen, as the carcinogenic efFect of D.M.B.A.…”
Section: Disgussionsupporting
confidence: 88%
“…2, Group II), and confirms similar findings by Shay, Harris and Gruenstein (1960). This characteristic is also shared by human breast cancer, the incidence of which is significantly reduced by oophorectomy before the age of 40 (Feinlieb and Garrison, 1969). This study also suggests that the protective effect of oophorectomy is due to reduction of circulating oestrogen, as the carcinogenic efFect of D.M.B.A.…”
Section: Disgussionsupporting
confidence: 88%
“…Several studies have shown oversaturation of cholesterol in cancer cells and low plasma cholesterol in malignancy . Therefore, a detailed study to understand the mechanism underlying the differential cholesterol homeostasis with immune cells vs tumor developing cells are needed to be explored in the future to target the therapeutic strategy of cancer.…”
Section: Discussionmentioning
confidence: 99%